PENGETAHUAN SOSIOLINGUISTIK SEBAGAI DASAR KETERAMPILAN KOMUNIKASI LISAN DI DALAM MASYARAKAT - Hastuti, Hastuti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
Sociolinguistics is a science that studies the use of language in society. Sociolinguistics is a discipline that is a blend of sosilogy and linguistics, the two disciplines are closely interconnected. Sociolinguistic discuss how language is used in the community, with whom we spoke, how the level of education, social status, or among government officials, education environmental or in our neighborhood that the language we use.Sociolinguistic is seen and approached as a language, but rather approached as a means of interaction or communication in society. By having knowledge of sociolinguistics, we can communicate well in the community, with opponents biacara see who we are, what level of education, for example, we can easily communicate with our speaker. The better the communication is done, the more the communication destination is reached. Communication objectives will be achieved well, if the intent were submitted were well received by our opponents said.